O conceito de “significatividade” em Ser e Tempo de Martin Heidegger - Vanny, Adel Fernando de Almeida (2009)
The present work aims at to rebuild the concept of significance , as it was presented in Being and Time of Martin Heidegger. Therefore, the concept should be characterized as formal structure of the worldhood of the world and, besides, while the foundation of the possibility of the word and, consequently, of the language. For that, we opted to treat the theme in three stages. In the first stage, we will look for to elaborate a brief presentation of the ontological project of Being and Time. This first chapter intends to place the theme of significance for inside of the heideggerian ontological project. Starting from the presentation of the heideggerian ontological project, the second stage has in mind the reconstruction of the significance while the formal structure of the Worldhood of the world. In that case, the second chapter will be centered in the analysis of the existential structure of the world, aiming at to expose the original constitution of the ontological structure of the world. While the third chapter aims at to characterize the significance as foundation of the possibility of the word and of the language. For that, this last stage will look for to explain the genesis of the language that is found in the ontological treaty Being and Time.